Stages of Development of Students' Creative Skills - Mamatkulova M.V (Zien Journals, 2022)
Development of creative abilities of students of higher education institutions, professionalpedagogical and methodical training, creation of conditions for the implementation of acquired knowledge, skills and qualifications, development of creative abilities of students, implementation of shortcomings and problems in the process of demonstrating creative abilities, as well as ways to eliminate them.
Keywords: psychological-pedagogical; technical-technological; dialectics; oral and visual